2018
DOI: 10.1111/mmi.14145
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine‐independent growth and biofilm formation, and functional spermidine/spermine N‐acetyltransferases in Staphylococcus aureus and Enterococcus faecalis

Abstract: Summary Polyamines such as spermidine and spermine are primordial polycations that are ubiquitously present in the three domains of life. We have found that Gram‐positive bacteria Staphylococcus aureus and Enterococcus faecalis have lost either all or most polyamine biosynthetic genes, respectively, and are devoid of any polyamine when grown in polyamine‐free media. In contrast to bacteria such as Pseudomonas aeruginosa, Campylobacter jejuni and Agrobacterium tumefaciens, which absolutely require polyamines fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 80 publications
(107 reference statements)
2
26
0
Order By: Relevance
“…Therefore, the in vitro substrate specificity showed spm is preferred over spd, which is similar to what has been observed in several previously characterized SSAT enzymes. 10,11,18 Previous studies with the human and mouse SSAT proteins showed that Y140 was critical for activity and it was proposed to act as a general acid during the enzymatic reaction. 6,15 Based on these results, Sugiyama et al mutated the structurally equivalent EcSpeG Y133 residue to phenylalanine in the recombinant protein and tested its activity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the in vitro substrate specificity showed spm is preferred over spd, which is similar to what has been observed in several previously characterized SSAT enzymes. 10,11,18 Previous studies with the human and mouse SSAT proteins showed that Y140 was critical for activity and it was proposed to act as a general acid during the enzymatic reaction. 6,15 Based on these results, Sugiyama et al mutated the structurally equivalent EcSpeG Y133 residue to phenylalanine in the recombinant protein and tested its activity.…”
Section: Resultsmentioning
confidence: 99%
“…Polyamines, such as spermidine and norspermidine, also have a dual role. Compounds that structurally mimic norspermidine has been demonstrated to effectively inhibit the biofilm formation of Bacillus subtilis and S. aureus [ 156 ], while both spermidine and norspermidine will also induce biofilm formation in some cases [ 157 , 158 , 159 ]. Besides, four D-amino acids produce by bacteria, including D-tyrosine, D-leucine, D-tryptophan, and D-methionine, can destroy existing biofilms and prevent biofilm forming [ 160 , 161 ].…”
Section: Dispersal Moleculesmentioning
confidence: 99%
“…Why might S. aureus and C. diphtheriae use the more complex amino acidcontaining structures rather than a putrescinecontaining one? It is well known that S. aureus is a putrescine auxotroph (57,58), and BLASTP analysis of C. diphtheriae strain proteomes indicates that no known putrescine synthesizing enzymes (52) are encoded in their genomes, in contrast to the putrescine prototrophs R. pickettii (59) and L. pneumophila.…”
Section: Putrescine Prototrophy and Putrescinedependent Rhizoferrin Bmentioning
confidence: 99%